(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This thesis examines modern methodological approaches to organizing English language lessons based on national Uzbek folklore, including proverbs, fairy tales, riddles, and folk songs. It substantiates that integrating folklore materials with communicative, project-based, and intercultural approaches effectively develops students’ English language competence. The paper presents the scientific basis of folklore-based language teaching grounded in psycholinguistic theories, outlines practical methods for incorporating each folklore genre into lessons, and explores opportunities for integration with digital technologies.